NILAI EDUKATIF DALAM NOVEL ANAK “JEJAK PUTIH DI TANAH BASAH” KARYA TRIA AYU KUSUMAWARDHANI (Educative Messages In Childrens Literary “Jejak Putih Di Tanah Basah” By Tria Ayu Kusumawardhani) - Rini Widiastuti (SAWERIGADING, 2009)
Literary work is a mind expression, idea, spirit and someone experience that contain of messages which could guide human being as a God creature, certain in religion dimension, social and human nature. The messages that could guide poeple to reach perfectly spirital generally such as mind and human kind hearted. Furthermore, it becomes the principle that underlay the human live, until the human carries wise, grew up and virtuous, is called educative messages. This writting aims to reveal theeducative messages that contained in childrens literary “Jejak Putih Di Tanah Basah” by Tria Ayu Kusumawardhani using qualitative descriptive method. Some of those educative messages such as keep worship to Allah, diligence, be loyal or dedication to his parent, creative, and  honesty.